Sistem permohonan lesen perniagaan dan pengurusan dokumen jabatan kesihatan dan lesen Majlis Perbandaran Johor Bahru Tengah (MBJBT) berasaskan web - Ab. Jalil, Haryanti (2005)
The main objective to build this system is to provide an easy way for the customer who is trying to apply for license yet needlessly for them to go to the counter. The systems will be focusing on document management at Health and License. Department and business license application. Rational Unified Process will be using as a methodology and Unified Modeling Language are using based on object designing. By having this system it will help the Health and License Department on managing their activities yet provided an efficiencies and reliable service.